The glucose-to-potassium ratio: a predictor of poor functional outcomes in stroke patients receiving thrombolytic therapy - Zhang, Dong; Ma, Ruinan; Qin, Xiaoyan; Li, Zhizhang; Zhang, Xiaoguang; Ding, Ying; Hu, Yunqi; Yue, Yunhua (Frontiers in Neurology, 2025)
BackgroundThe glucose-to-potassium ratio has shown promise as a biomarker in neurological disorders, but its prognostic value in acute ischemic stroke (AIS) after intravenous thrombolysis (IVT) continues to be uncertain. The study explores the relationship between admission GPR and 90-day functional outcomes in AIS patients undergoing IVT treatment.MethodsA retrospective analysis included 649 AIS patients undergoing IVT between May 2016 and December 2023. Baseline clinical, laboratory, and imaging data were analyzed. GPR was calculated from serum glucose and potassium levels at admission. A modified Rankin Scale score of 3 to 6 at 90 days was used to define poor functional outcomes. Logistic regression and restricted cubic splines assessed the GPR-outcome relationship, adjusting for confounders. Receiver operating characteristic (ROC) analysis evaluated GPR’s predictive value.ResultsAmong 649 patients, 174 (26.8%) had poor outcomes. Median GPR was significantly higher in these patients (2.14 vs. 1.88, p < 0.001). Higher GPR independently predicted negative consequences (OR, 1.821; 95% CI, 1.340–2.473, p < 0.001). Subgroup analysis indicated a stronger association in non-diabetic patients. ROC analysis demonstrated an area under the curve (AUC) of 0.631 (95% CI, 0.585–0.677, p < 0.001) for GPR in predicting poor functional outcomes.ConclusionHigh GPR levels are independently linked to unfavorable 90-day functional outcomes in AIS patients who received IVT, suggesting its potential as a prognostic biomarker. Further studies are warranted to validate these findings.